2012
DOI: 10.1097/wnr.0b013e328359d990
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo evidence for the disruption of Rab11 vesicle transport by loss of huntingtin

Abstract: The neuropathology of Huntington's disease includes nuclear and cytoplasmic inclusions, striatal neuronal loss, and gliosis. Previous work put forward a tantalizing proposal that disruption of axonal transport within long, narrow-caliber axons caused accumulations that could elicit cell death, ultimately resulting in neuronal dysfunction. Although a role for the Huntington's disease protein huntingtin (HTT) has been reported in axonal transport, it is unclear whether HTT affects the transport of all vesicles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
4
27
0
Order By: Relevance
“…We speculate that colocalization of eGFP-Pk pk and Kinesin might be due to traffic jams (axonal blockages) of the Kinesin-associated vesicles that have accumulated at the sites of Pk pk function (17,18) owing to the eGFP-Pk pk overexpression (staining of control larvae for Kinesin does not reveal Kinesin-positive axonal blockages or puncta). It is important to note that axonal blockages are oftentimes seen when genes encoding proteins known to be involved in axonal transport are either reduced in dosage [such as amyloid precursor protein-like (Appl), Khc, Kinesin light chain (Klc), and dynein heavy chain (17,19,21)] or overexpressed [such as Appl (17)]. Therefore, our data are consistent with both Pk pk and Kinesin functioning at the level of the MT to help promote vesicle transport.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that colocalization of eGFP-Pk pk and Kinesin might be due to traffic jams (axonal blockages) of the Kinesin-associated vesicles that have accumulated at the sites of Pk pk function (17,18) owing to the eGFP-Pk pk overexpression (staining of control larvae for Kinesin does not reveal Kinesin-positive axonal blockages or puncta). It is important to note that axonal blockages are oftentimes seen when genes encoding proteins known to be involved in axonal transport are either reduced in dosage [such as amyloid precursor protein-like (Appl), Khc, Kinesin light chain (Klc), and dynein heavy chain (17,19,21)] or overexpressed [such as Appl (17)]. Therefore, our data are consistent with both Pk pk and Kinesin functioning at the level of the MT to help promote vesicle transport.…”
Section: Resultsmentioning
confidence: 99%
“…One such study examined the dependency of YFP::Rab5 associated vesicles and YFP::Rab11 associated vesicles on endogenous Htt using live time-lapse imaging to track their dynamics (Power et al, 2012). Bi-directional transport of YFP::Rab11 associated vesicles was significantly slowed in larval neurons, while the transport rate of YFP::Rab5 associated vesicles was unaffected.…”
Section: Visualization Of Tagged Httmentioning
confidence: 99%
“…Importantly, in mammals, in contrast to the silencing or depletion of molecular motors, HTT silencing reduces but does not totally block axonal transport of cargo and does not result in the accumulation of axonal organelles. Finally, a recent study reported a defect in the dynamics of Rab11 but not Rab5 vesicles in Drosophila larvae in which DmHTT was silenced by RNAi [27]. These results suggest that DmHTT could play an important role in flies.…”
Section: Introductionmentioning
confidence: 77%
“…Three studies have investigated the function of Drosophila HTT (DmHTT) in axonal transport [24], [26], [27] but there are discrepancies between their findings. Silencing DmHTT by sh-RNA resulted in accumulation of axonal organelles, characteristic of severe transport defects [24].…”
Section: Introductionmentioning
confidence: 99%